218k views
1 vote
G(1)=-5
g(2)=3
g(n)=g(n-2)+g(n-1)
g(3)=?

User Arif Arifi
by
5.0k points

2 Answers

7 votes

Answer:

-2

Explanation:

User Betty Crokker
by
5.6k points
6 votes

Answer:

g(3) = -2

Explanation:


g(1)=-5\\g(2)=3\\g(n)=g(n-2)+g(n-1)\\\\g(3)=?\\\\\text{Put}\ n=3\ \text{to the formula of}\ g(n):\\\\g(3)=g(3-2)+g(3-1)=g(1)+g(2)\\\\\text{Substitute given value of}\ g(1)\ \text{and}\ g(2):\\\\g(3)=-5+3=-2

User Gomiero
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.